2019
DOI: 10.3390/molecules24030504
|View full text |Cite
|
Sign up to set email alerts
|

Structural Asymmetry and Kinetic Limping of Single Rotary F-ATP Synthases

Abstract: F-ATP synthases use proton flow through the FO domain to synthesize ATP in the F1 domain. In Escherichia coli, the enzyme consists of rotor subunits γεc10 and stator subunits (αβ)3δab2. Subunits c10 or (αβ)3 alone are rotationally symmetric. However, symmetry is broken by the b2 homodimer, which together with subunit δa, forms a single eccentric stalk connecting the membrane embedded FO domain with the soluble F1 domain, and the central rotating and curved stalk composed of subunit γε. Although each of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 165 publications
(296 reference statements)
2
21
0
Order By: Relevance
“…We observe an uneven distribution of particles between the three major rotary states, with 52% in state 1, 23% in state 2, and 21% in state 3, in line with other recent cryo-EM studies of ATP 3 of 10 (11)(12)(13) and with a recent singlemolecule study (20) that reported an asymmetry in the time-averaged population of rotary states in the presence of ADP. In comparing substates of a given primary rotary state, the later substates of the Polytomella complex (1D, 1E, 1F, 2C, 2D, and 3C) are consistently less populated than the earlier substates ( fig.…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimersupporting
confidence: 92%
“…We observe an uneven distribution of particles between the three major rotary states, with 52% in state 1, 23% in state 2, and 21% in state 3, in line with other recent cryo-EM studies of ATP 3 of 10 (11)(12)(13) and with a recent singlemolecule study (20) that reported an asymmetry in the time-averaged population of rotary states in the presence of ADP. In comparing substates of a given primary rotary state, the later substates of the Polytomella complex (1D, 1E, 1F, 2C, 2D, and 3C) are consistently less populated than the earlier substates ( fig.…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimersupporting
confidence: 92%
“…However, the proportion of particles corresponding to each reconstruction differed from our previous study (33% State 1, 44% State 2 and 23% State 3 in this study, compared with 46% State 1, 30% State 2 and 24% State 3 in Sobti et al, 2016), suggesting that a larger number of molecules were now observed in State 2 rather than State 1. Single molecule studies have also observed the enzyme populating the rotational dwell states in different proportions (Sielaff et al, 2019), suggesting that each dwell state may be at a different energy minimum. Inspection of the nucleotide-binding pockets in the α and β subunits revealed two further peaks, in addition to the four nucleotide peaks we reported previously for the autoinhibited enzyme (Sobti et al, 2016) (Figure 1—figure supplement 7).…”
Section: Resultsmentioning
confidence: 99%
“…The low, medium, and high efficiencies of TD formation reported here ( Fig 2B ) were attributed to torsional strain resulting from the asymmetry between 36° c 10 -ring stepping, and the 120° F 1 power strokes (8). Based on this asymmetry observed in low resolution ADP-inhibited F 1 F o structures (26), high efficiency TD formation was proposed to occur (27) in the rotary state comparable to that in which rotary sub-state structures PDB-IDs 6OQR and 6OQS were subsequently observed at 3.1 Å resolution (17). Sobti et al .…”
Section: Discussionmentioning
confidence: 98%